2001
DOI: 10.1017/s0317167100052835
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Parkinson's Disease in Urban Population of Southern Israel

Abstract: ABSTRACT:Background:In recent years, an increased prevalence of Parkinson's disease (PD) in southern Israel was observed. The aim of this study was to determine which exposures are associated with PD in the urban population of this region.Methods:Ninety-three PD patients living in towns were compared to 93 age and sex matched controls. A previously validated questionnaire, including demographic data, education, data on exposures, previous diseases, family history and habits, was administered.Results:In multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 19 publications
(20 reference statements)
1
48
1
Order By: Relevance
“…Results from a number of epidemiological and case-controlled studies appear to indicate a positive correlation between early exposure to pesticides and development of PD (Gorell et al, 1998;Ritz and Yu, 2000;Herishanu et al, 2001). Experimentally, several groups have reported recently that administration of pesticides and/or related agrochemicals results in the degeneration of the nigrostriatal dopaminergic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from a number of epidemiological and case-controlled studies appear to indicate a positive correlation between early exposure to pesticides and development of PD (Gorell et al, 1998;Ritz and Yu, 2000;Herishanu et al, 2001). Experimentally, several groups have reported recently that administration of pesticides and/or related agrochemicals results in the degeneration of the nigrostriatal dopaminergic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various environmental factors suspected to play a role in the pathogenesis of PD, exposure to agrochemicals has been most intensely investigated (Gorell et al, 1998;Ritz and Yu, 2000;Herishanu et al, 2001;Priyadarshi et al, 2001). A number of groups have reported that administration of herbicides such as rotenone and paraquat induces parkinsonism in rodents (Betarbet et al, 2000;Thiruchelvam et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…One study reported an OR of 7.0 (p value <0.05) [289] and another an OR of 10.9 (95% CI 2.5-48.0) [301]. The remaining 19 case-control studies that analyzed results from pesticide exposure overall reported no association [131,136,137,141,142,144,145,[305][306][307][308][309][310][311][312][313][314][315][316][317].…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Three case-control studies [137,141,434], one with prospective data nested within the Leisure World Cohort, California [434], reported lower risk of PD in relation to hypertension (OR 0.3, 95% CI 0.2-0.4 [141]; OR 0.48, 95% CI 0.26-0.88 [137]; OR 0.71, 95% CI 0.56-0.89 [434]). …”
Section: Vascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation